2021
DOI: 10.1177/19322968211049800
|View full text |Cite
|
Sign up to set email alerts
|

Green Diabetes Summit 2021

Abstract: On July 21, 2021, Diabetes Technology Society convened the virtual Green Diabetes Summit. The event consisted of 23 representatives from key stakeholder groups based in both the United States and Europe. The purposes of the summit were to (1) provide background on the complexity of addressing sustainability-related issues, including waste management, of diabetes devices from many different perspectives along the products’ life cycle stages, and (2) determine the feasibility and role of a coalition of stakehold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…To the best of our knowledge, there was no data available about home disposal practices of medical sharps in the Portuguese diabetic population, as in many other countries 20. We found clear evidence of inadequate disposal of medical sharps among these patients, findings that are corroborated by studies in the same scope conducted in other countries, which reported household bin disposal of medical sharps ranging from 33% to 92%,3 7 8 10 13 15 17 18 21–28 a common problem worldwide 9. Our results show that over two-thirds of diabetic patients discard sharps directly into common household bins.…”
Section: Discussionsupporting
confidence: 76%
“…To the best of our knowledge, there was no data available about home disposal practices of medical sharps in the Portuguese diabetic population, as in many other countries 20. We found clear evidence of inadequate disposal of medical sharps among these patients, findings that are corroborated by studies in the same scope conducted in other countries, which reported household bin disposal of medical sharps ranging from 33% to 92%,3 7 8 10 13 15 17 18 21–28 a common problem worldwide 9. Our results show that over two-thirds of diabetic patients discard sharps directly into common household bins.…”
Section: Discussionsupporting
confidence: 76%
“…4 As part of this commitment, in July 2021, the DTS convened the Green Diabetes Summit. The virtual event brought together 23 representatives from the USA and Europe, 5 including Professor Lutz Heinemann, CEO, Science Consulting in Diabetes, Kaarst, Germany.…”
Section: Green Diabetes Summitmentioning
confidence: 99%
“…3 Now 50 years after the Woods Hole report, a collaboration including medical specialists, environmental health experts and manufacturers seems set to reduce the environmental footprint left by plastics used in diabetes care. 4,5 After all, disposable diabetes devices -such as needles, syringes and pens, lancets, blood glucose monitoring strips and monitors, continuous glucose sensors, insulin bottles, infusion tubing, disposable pumps and batteries -create enormous amounts of plastic and other waste. 4 Yet the diabetes care product may represent only 10% of the total weight and volume.…”
mentioning
confidence: 99%
“…29,30 On July 21, 2021, Diabetes Technology Society convened the Green Diabetes Summit (GDS), a milestone event to discuss for the first time in an international forum how diabetes affects the environment. 31 The GDS assembled healthcare professionals, representatives from patient organizations, waste management experts, government agencies, and device manufacturers from the U.S. and six European countries. The purposes of the GDS were (1) to provide background on the complexity of diabetes device sustainability and waste management from a variety of perspectives, and (2) to determine the feasibility and role of a coalition of stakeholders to address issues in sustainability and waste management that no single stakeholder can resolve on their own.…”
Section: The Green Initiative To Reduce Plastic and Insulin Wastementioning
confidence: 99%